Carvão ativado a partir de resíduo têxtil: síntese, caracterização e aplicação na remoção de corante reativo e disperso em efluente têxtil - Bueno, Luana Maria Moreira Godoy (2023)
It is estimated that the textile industry consumes 98 million tons of non-renewable resources each year, before reducing environmental impacts of textiles is a challenge that the entire textile chain must undertake, from the choice of products to be used in its processes, wastewater treatment, as well as, the reuse of raw materials. The adsorption process has become one of the main techniques in industrial effluent treatment methods, being one of the most effective methods. Activated carbons are one of the adsorbent materials most used in adsorption processes to remove organic and inorganic contaminants. Various low-cost alternative adsorbents produced from agricultural solid waste, industrial solid waste, agricultural by-products and biomass are used as adsorbents for the adsorption treatment of dye wastewater, including textile industrial waste. Therefore, in the present work it was proposed the production of a carbonaceous material using textile residue (filter powder), for application in the removal of dyes. The activated carbon (CA) obtained was chemically activated with H3PO4 and produced by the slow pyrolysis process, resulting in a satisfactory yield (52.72±0.125%), was characterized by thermogravimetric analysis (TGA), Fourier transform infrared (FTIR), scanning electron microscopy (MEV), N2 adsorption-desorption isotherms, point of zero charge (pHPCZ) and used as adsorbent material in aqueous solutions of reactive yellow 160 dye and disperse yellow 211 dye. The produced CA presented BET specific area (SBET=2146.719 m2/g). The adsorption tests showed a removal of 89% for the reactive dye solution, 50% for the disperse dye solution and 67,51% for a third solution containing both types of dyes. Thus, the results obtained suggest the feasibility of using this textile waste as a precursor material for the production of CA and its applicability in the removal of textile dyes.